2013
DOI: 10.1002/adma.201303252
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated Copper(I) Carboxylates as Advanced Tunable p‐Dopants for Organic Light‐Emitting Diodes

Abstract: Volatile copper(I) benzoates with variable degrees of fluorination are used for p-doping of organic hole-transport layers in single-carrier devices, charge-generation layers, and in organic light-emitting diodes. The charge-transport abilities of the doped materials correlate with the degree and position of the fluorination on the aromatic ring of the carboxylate groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7] Superseding the early concepts of doping of semiconducting polymers with halogen vapors, a reasonably stable p-type doping wileyonlinelibrary.com studied the optical and charge carrier transport properties of various Lewis basic conjugated molecules and polymers which were doped by the strong Lewis acid tris(pentafl uorophenyl)borane (BCF). [ 31 ] The doping has been explained in terms of the formation of Lewis acid-base adducts. [26][27][28]30 ] BCF-doping of a copolymer of dithienosilole and pyridine units (DTS-Py) led to both changes of the polymer's optical properties and an increase of the free charge carrier concentration and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Superseding the early concepts of doping of semiconducting polymers with halogen vapors, a reasonably stable p-type doping wileyonlinelibrary.com studied the optical and charge carrier transport properties of various Lewis basic conjugated molecules and polymers which were doped by the strong Lewis acid tris(pentafl uorophenyl)borane (BCF). [ 31 ] The doping has been explained in terms of the formation of Lewis acid-base adducts. [26][27][28]30 ] BCF-doping of a copolymer of dithienosilole and pyridine units (DTS-Py) led to both changes of the polymer's optical properties and an increase of the free charge carrier concentration and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…This represents ar are example of as tepwise controlled chain growth in extended metal atom chains (EMACs). [6] Recently,t heoretical studies indicated that multicopper coordination to DNAb ase pairs may improve the conductivity of DNA-based nanowires. [1] Furthermore,o ne-dimensional (1D) assemblies of transition-metal complexes ("molecular wires") are of high interest for molecular microelectronics applications and studying processes of electron transfer in metal chains.…”
mentioning
confidence: 99%
“…[1] Furthermore,o ne-dimensional (1D) assemblies of transition-metal complexes ("molecular wires") are of high interest for molecular microelectronics applications and studying processes of electron transfer in metal chains. [6] Recently,t heoretical studies indicated that multicopper coordination to DNAb ase pairs may improve the conductivity of DNA-based nanowires. [2b, 3] In addition, Cu I "wires" and clusters of various nuclearities have been shown to have interesting photophysical properties that render them suitable for optoelectronic applications.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in agreement with our hypothesis that the doping effect increases with increasing acidity of a Lewis-acid. 18 In principle, the doping behavior of fluorinated copper acetylacetonate compounds can be explained by two mechanisms. First, copper in the oxidation state two can act as classical oxidant or electron acceptor and thus dope by electron transfer from the HOMO of the HTL to the LUMO of the dopant.…”
mentioning
confidence: 99%